BUILDING THE STUDENT CHARACTER THROUGH OUTDOOR ACTIVITY TO UNIVERSITY STUDENTS - Riadi, Muhammad Fajar; Nurhajati, Diani (Jurnal Pendidikan Bahasa Inggris Proficiency, 2025)
In the world of education, teaching literature is not only aimed at introducing literary works, but also at shaping students' characters through understanding the values. One of the ways to do that is conducting outdoor activity, which provides direct and contextual experience in connecting literature with real life. The objective of the research is to describe the strategies to build students’ characters in Introduction to Literature course through outdoor activity at University of Nusantara PGRI Kediri. This research used qualitative approach in which the subjects included the course lecturer and two students who participated in the outdoor activity. To collect data the researcher employed observation in the field, interviews, and document analysis. The study found that in the outdoor activity took place at Joyoboyo Forest Park Kediri. At the end of the activity, the students produced poems as the project. The activities, such as environmental observations, group discussions, and writing environmental-themed poems could build students’ character. Those activities developed the characters such as cooperation, responsibility, tolerance, discipline, and environmental awareness. The researcher recommended to other lecturers to do further integration of main course materials and outdoor activities, as it helped the students understand the materials of the course easily.